A non- unionised social work profession in the Republic of South Africa: implications for policy and practice - Kwakwa, Winnifred Mabel Motshidisi (My University, 2024)
The primary focus of this study was on non-unionisation of the social work profession in South Africa. On a secondary level, the study examined the history of the social work profession and unionisation, the evolvement of the profession itself since its inception to the current status and its intersectionality with gender, identity, status and image both locally and globally. The study triangulates three designs, which are Grounded Theory, Multiple case studies and exploratory design. Data was collected using semi-structured interviews from social workers who were part of the defunct social work union committee and alumni in Limpopo and those of the general social work practitioners in South Africa in their respective private spaces, to acquire a broader understanding of the phenomenon. Data was analysed thematically using thematic analysis. The general consensus was that a union is a necessity however, disunity and fragmentation of the profession, is still a thorny issue. The legacy of the South African history was fingered as perpetuating the disunity and fragmentation of this profession. In addition, the colonial social work curriculum that failed to prepare students for political activism and also the critical lens towards systemic and neo-liberal realities of today that are viewed to be exacerbating the status quo. The use of post-modernism (constructivism) and grounded theory enabled the development of a model of the social work union in South Africa based on the data and scenario provided by participants. The study is envisaged to set a way forward for more inquiry into the unionisation of the social work profession in other provinces, and to create further debate on the critical and radical field of social work and prospects of forming a union based on the proposed conceptual model.
Thesis (Ph.D. (Social Work)) -- University of Limpopo, 2024
Keywords: Unionisation; Social Work profession; South Africa; Grounded theory; Model; Professional practice; Social service; Practice (Philosophy); Social service -- Vocational guidance